2000
DOI: 10.1046/j.1440-1746.2000.02233.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of serum hyaluronic acid in patients with chronic hepatitis C and its relationship to liver histology

Abstract: Serum HA measurement may be clinically useful to non-invasively assess the degree of fibrosis and cirrhosis. Further prospective studies are warranted to determine the clinical utility of HA as a non-invasive marker of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
158
1
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(167 citation statements)
references
References 26 publications
6
158
1
2
Order By: Relevance
“…Furthermore, to evaluate diffuse liver diseases in a reliable manner, a specimen sample measuring at least 15 mm is needed. 24 Bedossa et al 7 showed recently that only 65% of biopsies relying on 15-mm samples led to correct diagnoses (using the METAVIR score), whereas 75% of biopsies relying on 25-mm samples were correct. Because there were no benefits to taking bigger samples, the investigators suggested that 25-mm samples are necessary to evaluate fibrosis accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to evaluate diffuse liver diseases in a reliable manner, a specimen sample measuring at least 15 mm is needed. 24 Bedossa et al 7 showed recently that only 65% of biopsies relying on 15-mm samples led to correct diagnoses (using the METAVIR score), whereas 75% of biopsies relying on 25-mm samples were correct. Because there were no benefits to taking bigger samples, the investigators suggested that 25-mm samples are necessary to evaluate fibrosis accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Vários estudos têm utilizado o AH como preditor de fibrose nos pacientes com HCC (7,12,13,15,27) . Nossos achados corroboram os de Halfon et al (7) , que reuniram 405 portadores de HCC para avaliar a acurácia desse marcador em predizer o estádio da fibrose hepática, e concluíram que o AH poderia ser usado clinicamente como marcador não-invasivo para fibrose e/ou cirrose.…”
Section: Discussionunclassified
“…Studies have demonstrated that HA levels correlate with the degree of hepatic fibrosis in patients with chronic HCV. 39,83,84 In alcoholic liver disease, the levels of HA correlate with both the degree of fibrosis and the severity of inflammation. 85 There is a direct linear relationship between HA and procollagen type III amino-terminal peptide (PIIINP) with similar performance by both tests in discriminating between alcoholic patients with and without liver fibrosis.…”
Section: Hamentioning
confidence: 99%